(untitled) (Journal of Dhaka Medical College, 2024)
Background: Soft tissue coverage of distal leg and ankle region represents a challenge and such defect usually requires a free flap. However, this needs facility of microsurgery, may lead to donor site morbidity and is time consuming. With the introduction of perforator flap, management of small and medium size defects of distal leg and ankle region is easier, less time consuming, and with minimal donor site morbidity. When local perforator flap is designed as propeller and rotated to 180-degree, donor site can be closed primarily and increases the distance crossed by flap, thus increasing versatility. Objectives: To observe the outcome of soft tissue coverage of defects around ankle joint by posterior tibial artery perforator based propeller flaps. Methods: This was a prospective type of observational study carried out on 20 patients with skin and soft tissue defects in and around ankle joint for a period of 14 months in the Department of Burn and Plastic Surgery, Dhaka Medical College and Hospital. Results: Among 20 cases 17 were male and 3 females; age ranged from 11 to 60 years. Post operative outcome of flap were excellent in 11 cases, good in 6 cases, poor in 3 cases as per defined criteria. Uneventful outcome was observed in 14 cases and minor complications were observed in 5 cases; and total flap loss occurred in 1 case which required revision surgery. Conclusions: Perforator flap provides adequate soft tissue coverage for small & medium size wound around ankle. It is an easy, reliable & effective procedure with reasonable outcome. J Dhaka Med Coll. 2022; 31(2) : 243-250